15th AIAA/ISSMO Multidisciplinary Analysis and Optimization Conference 2014
DOI: 10.2514/6.2014-2042
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Evaluation of Multidisciplinary Derivatives Using a Graph-Based Problem Formulation in OpenMDAO

Abstract: The optimization of multidisciplinary systems with respect to large numbers of design variables is best pursued using a gradient-based optimization together with a method that efficiently evaluates coupled derivatives, such as the coupled adjoint method. However, implementing such a method in a problem with more than a few disciplines is time consuming and error prone. To address this issue, we develop an automated procedure for assembling and solving the coupled derivative equations that takes into account th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…The benefits of using analytic derivatives, as opposed to finite differencing, for this problem are highlighted in a recent publication . We found that despite care in deriving models with smooth output, global finite differencing was not good enough to converge many of the solutions.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The benefits of using analytic derivatives, as opposed to finite differencing, for this problem are highlighted in a recent publication . We found that despite care in deriving models with smooth output, global finite differencing was not good enough to converge many of the solutions.…”
Section: Methodsmentioning
confidence: 97%
“…The constitutive equations for a laminate sequence can be expressed as (5) * The study actually showed DLC 1.4 extreme direction change (EDC) as the condition producing the largest deflection; however, only a PI controller was used for speed regulation, and no controller logic was asserted for start-up and shutdowns. The controller response to ECD, had there been one, would have substantially reduced turbine loads and resulted in turbine shutdown in the event of an extreme direction change.…”
Section: Panel Bucklingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various design variables and constraints are involved in describing the blade aerodynamic shape and structural layout, as well as meeting the geometric, load, stress and strain, vibration, and fatigue requirements of the system. In a typical design example [2], up to 32 design variables and 102 constraints are adopted in optimizing a wind turbine, resulting in an extremely challenging design process.…”
Section: Introductionmentioning
confidence: 99%
“…One other hand, OpenMDAO has ability to subdivide a problem into groups or components and link their inputs and outputs, made it easier to decompose large and complex problems. OpenMDAO has been used to solve MDO problems in satellite design [8], wind turbine design [9], aircraft design [10] and aircraft trajectory optimization [11].…”
Section: A Open Mdao Frameworkmentioning
confidence: 99%